Long-Term Results of the Etiotropic Therapy of Subcompensed Liver Cirrhosis in the Outcome of Chronic Hepatitis C - P. O. Bogomolov; A. O. Bueverov; V. E. Bakirova; E. O. Lyusina; E. A. Fedosyina; S. V. Koblov; O. V. Sumtsova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The evaluation of long-term results of antiviral therapy (AVT) with ombitasvir/paritaprevir/ritonavir and dasabuvir in patients with noncompensated liver cirrhosis (LC) in the outcome of chronic hepatitis C.Material and methods. A retrospective analysis included the data from patients with subcompensated liver cirrhosis (LC) of HCV etiology (genotype 1b) (7–9 points of the Child-Pugh score) having received interferon-free antiviral therapy (AVT) with ombitasvir/paritaprevir/ritonavir and dasabuvir during 12 weeks from September to December 2015. In total, 66 patients (27 men and 39 women) received such a therapy, the median age was 56.4 years.Results. 147 weeks (IQR 56–156) following AVT completion, the long-term results were evaluated. At that time, 27 patients were available for observation. The assessment of liver function compensation using the Child-Pugh score showed improvement in 25 (93 %) patients. The assessment of laboratory data revealed a decrease in the median of total bilirubin by 13.6 μmol/l, as well as an increase in the median of serum albumin by 9.7 g/L and the median of platelets by 41,700/μl. Two deaths were reported due to hepatocellular cancer (HCC) and bleeding from esophageal varices. HCC was detected in 8 patients. Two patients underwent liver transplantation.Conclusion. AVT in patients with LC of HCV etiology is associated with a high frequency of virologic response. Longterm follow-up results indicate a significant improvement of liver function, but also a continuing high risk of developing complications of underlying disease, primarily HCC.